(untitled) (Journal of the College of Basic Education, 2022)
Mathematics is an important science because of its contributions to scientific and technical developments as well as On its role in developing talents and intuition, which is one of the oldest sciences known to man, given his need to her in the process of counting and measuring, and (Bell (1986) called her the Queen of Science because of her great connection with with all other branches of knowledge. (Bill (1986, 22) (1) Mathematics is one of the basic components curriculum at all stages.